Pencegahan Stunting Berbasis Komunitas: Pemberdayaan Kader melalui Pengolahan Kudapan Kelor di Wilayah Agronursing - Musviro Musviro; Nurul Hayati; Iis Rahmawati (GUYUB: Journal of Community Engagement, 2026)
Stunting has long-term impacts on physical growth, cognitive development, and increased risk of disease in children. In Lumajang Regency, the stunting prevalence in 2024 reached 23.4%, highlighting the need for community-based prevention efforts. This community service aimed to enhance cadres’ capacity in stunting prevention through the utilization of moringa as a local food resource in the agronursing area of Kutorenon Village. The location was selected based on the availability of moringa and the readiness of local health cadres. The program applied an Asset-Based Community Development (ABCD) approach with a pre-experimental design (pre-test and post-test) involving 50 cadres. Activities included education, discussion, demonstration, and mentoring in preparing moringa-based healthy foods such as moringa ice cream and nuggets.The results showed a substantial increase in cadres’ knowledge, with mean scores rising from 60 to 88, along with improved practical skills in nutritious food preparation. The program also improved complementary feeding practices at community health posts, contributing to better child nutritional intake as a protective factor against stunting. Evaluation across nine posyandu indicated that six (66.7%) developed sustainable moringa-based menu innovations. This program positively impacted community nutritional behavior and has the potential to reduce stunting risk through improved child nutrition based on local resources.